Essential amino acid-enriched whey enhances post-exercise whole-body protein balance during energy deficit more than iso-nitrogenous whey or a mixed-macronutrient meal: a randomized, crossover study - Gwin, J. A.; Church, D. D.; Hatch-McChesney, A.; Allen, J. T.; Wilson, M. A.; Varanoske, A. N.; Carrigan, C. T.; Murphy, N. E.; Margolis, L. M.; Carbone, J. W.; Wolfe, R. R.; Ferrando, A. A.; et al. (Journal of the International Society of Sports Nutrition, 2021)
Background: The effects of ingesting varying essential amino acid (EAA)/protein-containing food formats on protein kinetics during energy deficit are undetermined. Therefore, recommendations for EAA/protein food formats necessary to optimize both whole-body protein balance and muscle protein synthesis (MPS) during energy deficit are unknown. We measured protein kinetics after consuming iso-nitrogenous amounts of free-form essential amino acid-enriched whey (EAA + W; 34.7 g protein, 24 g EAA sourced from whey and free-form EAA), whey (WHEY; 34.7 g protein, 18.7 g EAA), or a mixed-macronutrient meal (MEAL; 34.7 g protein, 11.4 g EAA) after exercise during short-term energy deficit.